Morphological investigations on anthers and pollen grains of some quince cultivars - Nagy Tiborné Déri, Helga (Acta Biologica Szegediensis, 2011)
In the present study we investigated some pollen morphological characters and anther size of Cydonia oblonga. Anthers of cultivars with apple- vs. pear-shaped fruits were also compared. In 2005 the anthers of cultivars with oblate vs. suboblate pollen showed significant differences. Anthers of the oblate group were notably shorter and smaller in size, than those of the suboblate group. Equatorial area of pollen in the former group was also smaller. In 2006 P/E ratio of pollen also correlated with length, width and size of anthers. However, shape and size of pollen grains did not show any relationship in the latter year. Equatorial area of pollen grains was not connected with anther size in 2005-2006. Fruit shape correlated with pollen shape only in 2005. P/E ratio of pollen in cultivars with apple-shaped fruits was lower than in cultivars with pear-shaped fruits. We could not demonstrate any relationships between anther morphology and fruit shape of the investigated quince cultivars.